Digital Literacy for Teachers: The Key to Success in Modern Teaching - Syahruddin; Rusdi; A. Rurisfiani (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
Digital literacy is no longer an option, but rather a necessity for teachers in the modern era. Investing time and effort in improving digital literacy will provide long-term benefits for teaching careers and student success. The purpose of this study is to determine and analyze how digital literacy for teachers is the key to success in modern teaching. The research method used in writing this article uses library research, namely a method of collecting data by understanding and studying studies from various literature, such as books, journals, and other scientific articles. The results show that digital literacy for teachers is the ability to understand, use, and integrate digital technology effectively in the modern teaching process. Digital literacy is an ongoing process, where technology continues to develop, so teachers need to continue learning and are required to be adaptive to change. Approaches that teachers can take to improve digital literacy skills include two aspects: a conceptual approach and an operational approach. The conceptual approach focuses on aspects of cognitive and social-emotional development, while the operational approach focuses on the technical ability to use the media itself in the teaching process. Therefore, schools and educational institutions can support this through ongoing training, workshops, and providing access to the latest digital resources supported by teachers' awareness and adaptability to digital literacy as one of the keys to success in modern teaching.